2015
DOI: 10.1149/06801.0151ecst
|View full text |Cite
|
Sign up to set email alerts
|

Status of Solid Oxide Fuel Cell Development at Elcogen

Abstract: Elcogen is a manufacturing company of solid oxide fuel cell (SOFC) and solid oxide electrolysis (SOE) unit cells and stacks. The competitive advance of Elcogen unit cells and stacks are their performance characteristics at reduced operating temperatures between 600°C to 700°C. The unit cells and stacks are based on conventional material solutions and manufacturing processes, which together with reduced operating temperature, provide cost benefits both for Elcogen’s products and system integrators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 2 publications
0
10
1
Order By: Relevance
“…In G2P mode, the BOP components affect the system efficiency negatively. This was not the case in the previous studies [16,17], where the BOP hardware influenced negatively the plant efficiency in P2G mode, while the effect in G2P mode depended on the UF 12 . The modelling study revealed that it was possible to raise the SOC operating temperature from 650 °C assumed in previous studies [16,17] to 700 °C without having to increase the pressure.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…In G2P mode, the BOP components affect the system efficiency negatively. This was not the case in the previous studies [16,17], where the BOP hardware influenced negatively the plant efficiency in P2G mode, while the effect in G2P mode depended on the UF 12 . The modelling study revealed that it was possible to raise the SOC operating temperature from 650 °C assumed in previous studies [16,17] to 700 °C without having to increase the pressure.…”
Section: Discussioncontrasting
confidence: 78%
“…This is highly relevant, as state of the art SOC systems operate at ~750 °C [11,42]. The operating temperature of the system is therefore varied from 650 °C to 750 °C [10][11][12]. In this case, the H/C ratio is set to the minimum value required to avoid carbon formation inside the SOC (Figure 2(b)).…”
Section: Changing the Operating Temperature Of The Socmentioning
confidence: 99%
See 1 more Smart Citation
“…z-direction). This anisotropy of the substrate could be related to its manufacturing method by tape casting [64] that induces a privileged orientation as discussed in [65].…”
Section: Reconstructions and Microstructural Characterizationmentioning
confidence: 99%
“…Due to the conduction of oxide ions (O 2− ) through an electrolyte and the occurrence of electrochemical oxidation in an anode at high temperature above 600 °C, SOFCs can, in principle, directly use not only hydrogen but also hydrocarbon and alcohol fuels. Since 2011, Kyocera has successfully commercialized residential combined heat/power systems using flatten‐tubular anode‐supported SOFCs ; other manufacturers are also developing stationary SOFC systems using planar and tubular SOFCs . These systems have an external steam reformer to convert natural gas to hydrogen in advance.…”
Section: Introductionmentioning
confidence: 72%